Analisis Perbandingan Job Costing dan Activity-Based Costing dalam Penentuan Biaya pada Perusahaan PLTS - Ani Suryani; Melly Andini; Iin Rosini (Fakultas Ekonomi Universitas 45 Surabaya, 2026)
Cost determination is an important aspect in managing Solar Power Plant (PLTS) installation projects because it affects the efficiency of resource utilization and project cost control. Companies engaged in PLTS installation require an appropriate costing method to identify activities that consume the largest portion of project costs. This study aims to analyze the comparison between the Job Costing method and the Activity-Based Costing method in determining costs in a PLTS installation project. This research uses a descriptive method with a comparative approach. The data used in this study are project cost data obtained from the Bill of Material document of a PLTS installation project with a capacity of 446.4 kWp. The analysis was carried out by classifying project costs using the Job Costing method and allocating costs based on project activities using the Activity-Based Costing method. The results show that the total cost of the PLTS installation project is Rp3,403,452,664 with the largest component coming from material costs. Activity-based analysis indicates that the PLTS system installation activity consumes the largest portion of project costs. The findings indicate that the Activity-Based Costing method provides more detailed cost information related to project activities and can assist companies in improving cost control and enhancing efficiency in PLTS installation projects.